2017
DOI: 10.1016/j.tox.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor activation by 2,3,7,8-tetrachlorodibenzo-p-dioxin impairs human B lymphopoiesis

Abstract: The homeostasis of peripheral B cell compartment requires lifelong B lymphopoiesis from hematopoietic stem cells (HSC). As a result, the B cell repertoire is susceptible to disruptions of hematopoiesis. Increasing evidence, primarily from rodent models, shows that the aryl hydrocarbon receptor (AHR) regulates hematopoiesis. To study the effects of persistent AHR activation on human B cell development, a potent AHR agonist and known environmental contaminant, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) was utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
2
17
1
Order By: Relevance
“…In a prior study (34), we also observed decreased B lymphopoiesis with TCDD treatment using culture systems containing various stromal cell components; however, the magnitude of suppression was not as profound as in the current study. Differences in sensitivity to TCDD using the different culture systems are not surprising and can likely be attributed to several factors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In a prior study (34), we also observed decreased B lymphopoiesis with TCDD treatment using culture systems containing various stromal cell components; however, the magnitude of suppression was not as profound as in the current study. Differences in sensitivity to TCDD using the different culture systems are not surprising and can likely be attributed to several factors.…”
Section: Discussioncontrasting
confidence: 67%
“…Likewise, our prior studies using human CD34 + hematopoietic stem/progenitor cells (HSPC) have demonstrated an impairment of B lymphopoiesis by AHR activation (34). The underlying mechanism by which AHR regulates B lymphopoiesis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of PrimeFlow™ to measure gene specific mRNA on a per cell basis enables quantification of cell stage specific gene expression in transitional cell populations during hematopoiesis. For instance, we have reported that 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) treatment impairs the development of human hematopoietic stem/progenitor cells (HSPC) to lineage committed B cells(Li et al , 2017). To study the molecular mechanisms underlying the impaired B cell development, PrimeFlow™ was used to measure the changes in mRNA expression of lineage specific genes in the HSPC-derived heterogeneous cell population.…”
Section: Measuring Changes In Gene Specific Mrna Levels In Transitionmentioning
confidence: 99%
“…The regulation of gene expression is involved in almost every aspect of immune responses, including : 1) cytokine production and cell surface receptors expression after activation (Chen et al , 2012; Phadnis-Moghe et al , 2015; Henriquez et al , 2017; Li et al , 2017); 2) clonal expansion (Sablitzky et al , 1985; van Stipdonk et al , 2001); and 3) terminal differentiation into mature effector and memory cell types (Rissoan et al , 1999). The most ubiquitous and reliable method of gene transcriptional analysis is Real-Time Quantitative PCR (RT-qPCR).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental immunotoxicity can be evaluated using in vitro models capitalizing on the availability of human cord blood-derived hematopoietic stem cells. For example, in studying human B cell development, Li and coworkers [15] have used a combination of flow cytometry-based and cell culture-based approaches to show that the environmental contaminant TCDD decreased the total number of hematopoietic stem cells and lineage committed CD19 + B cells, suggesting the impairment of human B lymphopoiesis. This study illustrates another novel approach utilizing human primary cells as an adjunct to more traditional rodent based strategies.…”
Section: Current Approaches To Immunotoxicity Testing Using Primarmentioning
confidence: 99%